Enhancing Inclusive Education for Slow Learners in School Settings - Sisdiana, Etty; Nanji, Noor Soeseno Vijaya Krishna; Hendrawati, Sri; Jarwadi, Jarwadi; Widaryanto, Benny; Mustika, Ika (Journal International Inspire Education Technology, 2024)
Slow learners, identified as individuals with an IQ range of 69-89 and falling within the category of special needs children, necessitate inclusive education services tailored to their unique characteristics and learning requirements to facilitate their optimal development. These students often encounter challenges in grasping academic concepts, thereby necessitating specialized learning services and adequate resources within educational settings. While existing research has predominantly concentrated on curriculum design, instructional methodologies, and teacher readiness, customized learning resources remain insufficient. This study addresses the critical need to examine the accessibility of such resources in educational environments to inform the formulation of more inclusive and effective education policies that enable all children to unlock their academic potential fully. The research investigates the presence of suitable learning resources in inclusive schools for slow learners using a descriptive qualitative approach. Data were collected through interviews, Focus Group Discussions, and observations in two primary schools spanning five cities: Padang, South Tangerang, Bandung, Yogyakarta, and Malang. Key informants included school principals, classroom teachers, special education instructors, and assessments of available learning resources. The study findings highlight that slow learners may not be readily identifiable through physical observations and underscore the necessity for tailored resources to support their educational progress. Further research is essential to enhance understanding and address the needs of slow learners within inclusive educational frameworks.